Fewer STPM students with perfect scores: OVERALL RESULTS:However, national CGPA score increase from 2.62 to 2.65 last year - News Straits, Times (News Straits Times, 2016)
The were slightly fewer candidates scoring a perfect 4.0 cumulative grade point average (CGPA) in the Sijil Tinggi Persekolahan Malaysia (STPM) examination last year compared with the previous year.